De abdijtuinen van Averbode. - Historische continuïteit en landschappelijke franje - Deneef, Roger; Janssens, Herman; Wijnant, Jo; Schroeven, Chris (Monumenten en Landschappen, 2003)
Keywords: averbode

Maarsbergen. Van Proosdijhuis tot kasteel - Groningen, Catharina L. van (Bulletin van de Koninklijke Nederlandse Oudheidkundige Bond, 2003)
Discusses the history of the house, built as the deanery of monastic outbuildings of the Premonstratensian abbey of Berne near Heusden in 1134, and its park; the oldest parts of the present building date from the 15c.
Keywords: maarsbergen

De poldermolens van Mariënweerd - Jurgens, Nico (Abdijmolens tussen Rijn en Schelde, 2003)
Keywords: mariënweerd

Begeleiding van graafwerkzaamheden op 't Kloosterterrein in Oldekerk, Groningen - Schrijer, E. (2003)
Keywords: kuzemer

Het klooster van Schellebelle Gezeit 'Tussenbeke' - Van der Snickt, Conny (Rond de Stenen Linde, 2003)
Keywords: tussenbeek

Het Abdijcomplex te Middelburg architectonisch bedrog? - Zaceagnini-Visser, Rosa (Bulletin van de Koninklijke Nederlandse Oudheidkundige Bond, 2003)
Keywords: middelburg